(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The present article examines the fundamental aspects of English pronunciation, including phonetic transcription, vowel and consonant sounds, word stress, and intonation. Furthermore, it provides comparative examples from English, Uzbek, and Russian, highlighting common pronunciation difficulties encountered by non-native speakers. The article also discusses practical strategies for improving pronunciation skills and emphasizes the importance of phonetic competence in language learning and translation studies.